Yahoo Web Search

related to K.C

1. Sort by

1. What kind of industries can be found in Saint John, NB?

... provinces of Canada. Wealthy industrialist K.C. Irving and his family built an industrial conglomerate in the city...

1 Answers · Education & Reference · 05/06/2012

2. find y as a function of x if y'''+36y'=0 y(0)=-6 , y'(0)=-18, y''(0)=-36?

...solution is y(x) = c*e^(6i*x) + k*e^(-6i*x) + C. Now y(0) = c + k + C = -6. Next, y'(x) = 6i*c*e^(6i*x) - 6i*k*e^(-6i*x), so y'(0) = 6i...

1 Answers · Science & Mathematics · 24/02/2013

... first roll. Binomial probability formula: P(X=k) = C(n,k) * p^k * q^(n-k) p = 1/6 q = 5/6 n = number of dice ...

2 Answers · Science & Mathematics · 28/03/2018

4. Ghosts of Girlfriends Past soundtrack ?

... Casey and Richard Finch Performed by K.C. & The Sunshine Band Courtesy of Rhino...

1 Answers · Entertainment & Music · 04/07/2012

5. Half-life Help please!!?

You have for the decay a C-14 : dC/dt = ( -K ) ( C ) where C is concentration of the C-14. dC /C...

1 Answers · Science & Mathematics · 25/04/2010

6. Statistics probability question? (max points)?

... to use the notation of C(n,k), where: C(n,k) = n! / ((n-k)! k!) C(40,4) = 40 x 39 x 38 x 37 / (4 x 3 x 2 x 1) = 91390 ways PART...

2 Answers · Science & Mathematics · 04/10/2014

7. Given the equation, find the values of k such that the equation has...?

...an equation to have equal roots, the discriminant (b^2-4ac) must be 0 a=1 b=k c=(-k+8) k^2-4(1)(-k+8)=0 k^2+4k-32=0 (k+8)(k-4)=0 k=-8,4 2.For...

3 Answers · Science & Mathematics · 24/11/2010

8. is it halal for me to eat pig and drink sperm? Ass salami all eat cum.?

Reinsert your brain properly, kid. You'll be more coherent, then.

4 Answers · Entertainment & Music · 22/06/2016

9. 2NH(3) <----> N(2) + 3H(2)?

... for the balanced equation), we write the equilibrium expression K as: K = ([C]^c*[D]^d)/([A]^a*[B]^b) In other words, the ...

1 Answers · Science & Mathematics · 04/06/2012

10. Discriminant Question!?

b^2 - 4ac > 0 a = 4 b = -k c = 9 (-k)^2 - 4 * 4 * 9 > 0 k^2 - 144 > 0 (k + 12)(k - 12) > 0 k < -12 k > 12

1 Answers · Education & Reference · 01/11/2014